Electronic vs. Print Resources: A Survey of Perception, Usage and Preferences Among Central University Undergraduate Students - George Clifford Yamson; Antonia B. Appiah; Marian Tsegah (European Scientific Journal, ESJ, 2018)
The study adopted a cross-sectional survey approach to examine the perception, usage and preferences of electronic and print resources among University Students. The study sought to determine the knowledge of students on electronic library resources, their value for electronic and print resources, ascertain the perceived usefulness, perceived ease of use, and intended use these resources. Results from the study indicated that majority 134(57.0%) of the respondents always preferred print resources format for their academic work while 101(43%) occasionally preferred the electronic resource format for academic work. The findings of the study are critical to the implementation of policies and procedures geared toward sensitizing students, faculty and other stakeholders to the benefits of increasing students’ knowledge and use of electronic library resources. The study is envisaged to aid in strategic planning and investments pertaining to these resources and provide recommendations to improve knowledge and use of these resources within university.